Current perspectives and trends in acupuncture for sleep disorders: a bibliometric analysis - Huang, Yi; Ying, Xihan; Zhang, Jieqi; Hu, Rong; Chen, Yi; Wu, Lei; Chen, Bowen; Zhang, Kai; He, Kelin; Ma, Ruijie (Frontiers in Psychiatry, 2024)
Background: Limitations of conventional treatment methods for sleep disorders have driven the use and development of complementary and alternative therapies such as acupuncture. However, despite the surge in related studies, there is still a lack of visual analysis and detailed elaboration regarding the current status, international collaborations, and research hotspots of acupuncture for sleep disorders. Methods: We conducted a bibliometric analysis of publications on acupuncture for sleep disorders using the Web of Science Core Collection database from 2004 to 2023. We utilized the R package "bibliometrix" to count publications and citations, VOSviewer to create an inter-institutional referencing network, and CiteSpace to identify references and keywords with the highest citation bursts. Additionally, we employed a bibliometric online analysis platform designed for analyzing national partnerships. Results: A total of 432 pertinent papers were retrieved, with China being the most prolific contributor, accounting for 61.6% of the publications, followed by the United States and South Korea. Despite China's high output, its average article citation rate and proportion of international collaborations were notably lower than those of the United States. Key research institutions such as the